Allometric Equation for Estimating Energy Production of Eucalyptus urophylla in Dryland Ecosystems at East Nusa Tenggara - Ronggo Sadono; Wahyu Wardhana; Fahmi Idris; Pandu Yudha Adi Putra Wirabuana (Jurnal Manajemen Hutan Tropika, 2022)
A precise and accurate energy production quantification, particularly at the individual tree level is needed to understand the potential contribution of eucalyptus plantations to renewable energy development. However, measuring energy storage with a destructive method is inefficient because it requires a large amount of resources. The development of allometric equations is a realistic solution to solve this problem as it facilitates the efficient estimation of energy production from trees. Therefore, this study aims to develop an allometric equation for estimating the energy production of Eucalyptus urophylla in dryland ecosystems in East Nusa Tenggara. The destructive sampling was carried out on 25 sample trees which are evenly distributed from small to large dimensions, while the calorific value of each tree component was analyzed using the bomb calorimeter method. Furthermore, the energy production of each tree was counted by multiplying the calorific value with the total biomass accumulation. To develop an allometric equation, the analysis of regression was applied using several independent variables, such as diameter at breast height (D), combined squared diameter of breast and tree height (D2H), as well as D and H separately. The results showed that the energy production of E. urophylla at the study site varied from 252.56 to 7,813.30 MJ tree-1 with more than 90% accumulated in the stem, followed by foliage (4.62%) and branches (4.05%). The higher the tree dimension, the greater the energy production. Moreover, the equation lnŶ = lna + b.lnD + c.lnH was the best allometric model to estimate energy production with an accuracy of 95.2%. Based on the results, the allometric equation provides an accurate estimation of energy production in E. urophylla.